HIV epidemic among Brazilian women who have sex with women: An ecological study - Bezerra, Ana Luisa Lemos; Sorensen, William; Rodrigues, Taymara Barbosa; Sousa, Sara Melissa Lago; Carneiro, Márcia Simão; Polaro, Sandra Helena Isse; Ramos, Aline Maria Pereira Cruz; Ferreira, Glenda Roberta Oliveira Naiff; Gir, Elucir; Reis, Renata Karina; Botelho, Eliã Pinheiro (Frontiers in Public Health, 2022)
The influences of public policies fighting HIV among women who have sex with women is scarcely studied. This study aimed to analyse the time series of human immunodeficiency virus (HIV) epidemic, between 2007 and 2020, among Brazilian women who have sex with women, in order to evaluate the effect of Brazilian policies for fighting HIV in this subpopulation compared to women who have sex with men (WSM). This ecological study employed HIV and acquired immunodeficiency syndrome (AIDS) new cases among women who have sex strictly with women (WSW), women who have sex with men and women (WSMW), and WSM reported to the Sistema de Informação de Agravos de Notificação from 2007 to 2020. Crude Brazilian and regional annual age-adjusted HIV/AIDS population-level incidence rates were calculated for WSW, WSMW and WSM. The rates were then analysed using the Joinpoint regression model. A total of 102,890, 757, and 1,699 notifications of WSW, WSMW, and WSM living with HIV/AIDS were reported during the study period, respectively. South Brazilian region had the greatest HIV/AIDS incidence rates among WSM and bisexual women while the North region had the greatest incidence among WSW. In the WSM population, the temporal trends showed at least one stable or an increasing trend period from 2007 to 2013 or 2014, followed by one decreasing trend in all Brazilian regions. While among the bisexual population most of the regions had a stable trend period from 2007 to 2020, in WSW group most of the trends had only one decreasing period. The decreasing trends were faster in WSM than in WSW. These results suggest a low efficiency of Brazilian policies for fighting HIV among WSW and bisexual women and show the necessity of implementing new policies specific to this population.